Hubungan Pola Asuh Dengan Pertumbuhan Anak 6-24 Bulan (Studi Perbandingan Antara Suku Melayu Jambi Dan Suku Jawa Di Kabupaten Muaro Jambi Propinsi Jambi) - Tuhu Perwitasari (Universitas Batanghari Jambi, 2019)
One of factors that affect the growth of child is the nutritional status which determines the success in improving the quality of human resources. The health care and food in early life is crucial one to the growth and development of the child. This study aim to seek wheter the difference in child parenting between Jambi Malay and Javanese to the growth of children 6-24 months in Muaro Jambi District of Jambi Province is occured.The design of this study is observational analytic with cross sectional. The samples of the study were taken at two Working Areas of Health Care ; Muara Kumpeh for Jambi Malay and Markanding for Javanese Tribe. The population is children aged 6-24 months in both Working Areas of helath care and the number of samples taken in each area is 100 children. The data was collected through interviews and observations by researchers assisted by midwives in the helath care. Data processing was done using SPSS and data analysis using Mantel-Haenszel test.In this research, there is no disparity in parenting feeding methods (p = 0,227), while the analysis cannot be conducted on health parenting because there was a value of 0. Furthermore, there is no difference in parenting hygiene (p = 0.828), and there is a significant difference in parenting psychosocial stimulation (p = 0.000) in Jambi Malay and Javanese. In this study it can be concluded that there is a significant difference in the growth of the child 6-24 month at the Jambi Malay and Javanese. In addition, there is no difference in Jambi Malays and Javanese parenting to the grow of the child aged 6-24 month. So that,It is suggested to provide counseling and health counseling to the mother and also involves other family members such as father.